Regulatory Sanctions and Reputational Damage in Financial Markets - Armour, John; Mayer, Colin; Polo, Andrea (Journal of Financial and Quantitative Analysis, 2017)
We study the impact of the enforcement of financial regulation by the United Kingdom’s regulatory authorities on the market price of penalized firms. Existing studies rely on analyses of multiple events that may distort the measurement of reputational losses. In the United Kingdom, the entire enforcement process involves only one public announcement and is accompanied by complete information on legal penalties. We find that reputational losses are nearly nine times the size of fines and are associated with misconduct harming customers or investors but not third parties.